Compared to what: What can we say about nonapeptide function and social behavior without a frame of reference? - Kelly, Aubrey M. (Curr Opin Behav Sci, 2015)
Our understanding of behavior and mechanism is undermined by the absence of a frame of reference because relationships between individuals and species are without context. We highlight a need to be more comparative, using nonapeptide (vasopressin and oxytocin) modulation of social behavior as an example. We reconsider the use of model organisms and the term ‘social’ in this context, contrasting two popular models for nonapeptide regulation of social behavior. We then propose that a frame of reference should be established by studying mechanisms of behavior across taxa along the same continua. If we are to ever establish a unifying theory of behavior, we must transcend individual examples and determine the relative relationships of behavior and mechanism among and between species.